New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae) - Huerta, Herón; Haenni, Jean-Paul (Zootaxa, 2016)
Four new species of the recently described genus Aztecatopse Haenni & Huerta are described from Mexico. Three of them, Aztecatopse amorimi sp. nov., A. foliosa sp. nov. and A. spinosa sp. nov. occur sympatrically with the type-species of the genus in central region (state of Mexico), while A. neotropica sp. nov. has been collected in states of Guerrero, Jalisco and Morelos. A key to the males of all known species of the genus is provided.